PENGENDALIAN MUTU PRODUK UDANG BEKU ( FROZEN SHRIMP) MELALUI PENERAPAN HACCP PADA UNIT PENGOLAHAN IKAN (UPI) - Rezki Tri Ahzani; Andi Tamsil; Hasnidar Hasnidar (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
The objectives of this study are: 1) identifying critical points in the frozen shrimp processing process in several Fish Processing Units in Makassar City in particular. 2) Evaluate the quality control in frozen shrimp processing and how far it is in accordance with the HACCP (Hazard Analysis Critical Control Point) concept. 3) Evaluate the basic feasibility and level of HACCP implementation from the Fish Processing Unit. This research was carried out for 1 month from December 2023 to January 2024 at the fish processing unit (UPI) in the Makassar Industrial Estate (KIMA), Makassar City. The results of this study are 1) The results of the identification of critical points (CCP) in both UPIs are known that for UPI 1 at the Raw Material and Metal Detecting stages, it is stated as a critical point (CCP). At UPI 2 critical points (CCP) at the Raw Material, Metal Detecting and Labeling stages. The monitoring of the second CCP of UPI has implemented monitoring procedures, controlling critical points consisting of components: what, how, frequency, who. 2) Both UPIs have implemented quality control for handling frozen shrimp which can be seen from the results of organoleptic and microbiological tests (ALT, Salmonella, E.Coli and V. Cholerae) which show that the results do not exceed the threshold value of each parameter. The concept of HACCP by applying 7 HACCP principles by supervising and making preventive efforts on Standard Sanitary Operating Procedures (SSOP) and Standard Processing Operations (SOP). 3) Judging from the results of the basic feasibility of both UPIs, the Standard Sanitary Operating Procedures and the Standard Processing Operations in UPI 1 have a deviation condition of (Minor 4, Major 1) with a rating of A (Very Good) and in UPI 2 the condition of deviation is (Major 3) with a rating of A (Very Good).